Docking study: PPARs interaction with the selected alternative plasticizers to di(2-ethylhexyl) phthalate. (3rd May 2016) - Kambia, Nicolas; Farce, Amaury; Belarbi, Karim; Gressier, Bernard; Luyckx, Michel; Chavatte, Philippe; Dine, Thierry
Abstract: Phthalates, used in medical devices (MDs), have been identified as reproductive and developmental toxicants. Their toxicity varies somewhat depending on the specific phthalate and is in part linked to the activation of Peroxisome Proliferating-Activated Receptors (PPARs). So, the use of MDs containing targeted phthalates such as di(2-ethylhexyl) phthalate (DEHP) has been challenged by European directive 2007/47/EC. Therefore, MDs manufacturers were forced to quickly find replacement plasticizers. However, very little toxicological and epidemiological studies are available on human health. So, we proceeded to dock these chemicals in order to identify compounds that are likely to interact with PPARs binding sites. The results obtained are generally very mixed on the harmlessness of these alternatives. Moreover, no data exist on the biological effects of their possible metabolites. As DEHP toxicity resulted mainly from its major metabolites, generalizing the use of these plasticizers without conducting extensive studies on the possible effects on human health of their metabolites seems inconceivable.